2014
DOI: 10.4236/jst.2014.42007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Doping Level on the Characteristics of Piezoresistive Pressure Sensor

Abstract: Piezoresistive pressure sensors based on silicon have a large thermal drift because of their high sensitivity to temperature. The study of the effect of the temperature and doping level on characteristics of these sensors is essential to define the parameters that cause the output characteristics drift. In this study, we adopted the model of Kanda to determine the effect of the temperature and of doping level on the piezoresistivity of the Silicon monocrystal. This is to represent P(N,T) and ( ) This allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Temperature and doping levels in piezoresistors cause the most significant drift in the output characteristics of pressure sensors [25]. Considering the models available [26][27][28], the Kanda Model [29] has been selected due to the ease with which a good estimate of the piezoresistance coefficient can be computed [15,28].…”
Section: Characterization Of the Mfs Piezoresistive Gridmentioning
confidence: 99%
See 3 more Smart Citations
“…Temperature and doping levels in piezoresistors cause the most significant drift in the output characteristics of pressure sensors [25]. Considering the models available [26][27][28], the Kanda Model [29] has been selected due to the ease with which a good estimate of the piezoresistance coefficient can be computed [15,28].…”
Section: Characterization Of the Mfs Piezoresistive Gridmentioning
confidence: 99%
“…being the Fermi Energy in the doped p-type Silicon and Boltzmann's constant, The coefficient 44 used in the mathematical model of the MFS was derived using (13) and (14). Studies have revealed that:  Increasing doping concentration and/or temperatures respectively cause a lowering in piezoresistive sensitivity [25] and;  The estimation of the coefficient by Kanda's method is best for doping levels up to 5x10 19 atoms/cm 3 .…”
Section: ) the Piezoresistive Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…His study uses the electric drift for compensating offset thermal drift. In a previous paper [8] we have investigated the effect of temperature and doping level on the characteristics of such sensors. The approach to the compensation for temperature drift of offset voltage in this sensor type was proposed by U. Aljancic [7].…”
Section: Introductionmentioning
confidence: 99%